The Role of Molybdenum in the Formation of the Microstructure and Properties of Al-Cu Alloys - S. Stąpór; M. Górny; Ł. Gondek; B. Gracz; M. Kawalec (Archives of Foundry Engineering)
The subject of the presented research is the influence of molybdenum on selected properties of alloys that are based on the Al-Cu system. It could be observed that the introduction of molybdenum to the multi-component alloy at levels of up to 0.5 wt.% showed increases in the degrees of undercooling ΔT along with the increasing contents of the introduced element. The addition of molybdenum contributed to the reduction of the size of the primary grains of the α(Al) phase. Molybdenum improved the strength of the alloy while achieving elongation at a significant level. This is an element that occurs in the alloy – both in the iron-manganese phases and in the segregates inside the grains. Most of the iron-manganese phases occurred in a more spheroidal form. Additionally, tests were carried out on higher molybdenum content in the alloy. The addition of the tested chemical element at a level of 1 wt.% caused the precipitation of the phases that contained molybdenum, which did not dissolve after heat treatment.